La dramatisation de l’idée de l’Islande dans les médias contemporains - Chartier, Daniel (Nordiques, 2022)
Based on the hypothesis that a “place” is built by the dynamic between its material existence and the discourse on it, this article aims to study the image of Iceland in English and French foreign press in the context of the «post-crisis» of 2008. It appears that the image of Iceland is built, from the outside, from a perennial discourse based on seven main paradigms (Iceland as a strange, wonderful, distant, violent, and recently: progressive, egalitarian and environmentalist place) and global debates in which Iceland is discursively used to strengthen positions of interest to the different readerships of foreign newspapers. Some media crises promptly put the positive discursive image of Iceland to the test. During the analysed period (between 2014 and 2016), debates on the exponential growth of tourism, Brexit, Euro 2016, and “Panama Papers” create a dramatic tension between these issues and the common positive discourse on Iceland, which allows to better understand the perception of this country from abroad. S’appuyant sur l’hypothèse qu’un « lieu » se construit par la dynamique entre son existence matérielle et la somme des discours qui portent sur lui, cet article a comme objectif d’étudier l’image de l’Islande dans la presse étrangère de langues française et anglaise dans le contexte de l’« après-crise » de 2008. Il apparaît que l’image de l’Islande se construit, de l’extérieur, entre un discours pérenne qui s’appuie sur sept paradigmes principaux (l’Islande serait ainsi étrange, merveilleuse, lointaine, violente et depuis peu : progressiste, égalitaire et écologiste) et des débats mondiaux où l’Islande agit discursivement, en pure rhétorique, dans des prises de position liées aux intérêts des différents lectorats des journaux étrangers. Certaines crises médiatiques mettent ponctuellement le fonds discursif positif de l’Islande à l’épreuve. Durant la période analysée (soit entre 2014 et 2016), des débats sur la croissance exponentielle du tourisme, le Brexit, l’Euro 2016, et les « Panama Papers » créent ...